Mixture of Corni Fructus and Schisandrae Fructus improves testosterone-induced benign prostatic hyperplasia through regulating 5α-reductase 2 and androgen receptor - Hwangbo, Hyun; Kim, Min Yeong; Ji, Seon Yeong; Park, Beom Su; Kim, TaeHee; Yoon, Seonhye; Kim, Hyunjin; Kim, Sung Yeon; Jung, Haeun; Kim, Taeiung; Lee, Hyesook; Kim, Gi-Young; et al. (Nutrition research and practice, 2023)
Benign prostatic hyperplasia (BPH) characterized by an enlarged prostate gland is common in elderly men. Corni Fructus (CF) and Schisandrae Fructus (SF) are known to have various pharmacological effects, including antioxidant and anti-inflammatory activities. In this study, we evaluated the inhibitory efficacy of CF, SF, and their mixture (MIX) on the development of BPH using an model of testosterone-induced BPH. Six-week-old male Sprague-Dawley rats were randomly divided into seven groups. To induce BPH, testosterone propionate (TP) was injected to rats except for those in the control group. Finasteride, saw palmetto (SP), CF, SF, and MIX were orally administered along with TP injection. At the end of treatment, histological changes in the prostate and the level of various biomarkers related to BPH were evaluated. Our results showed that BPH induced by TP led to prostate weight and histological changes. Treatment with MIX effectively improved TP-induced BPH by reducing prostate index, lumen area, epithelial thickness, and expression of BPH biomarkers such as 5α-reductase type 2, prostate-specific antigen, androgen receptor, and proliferating cell nuclear antigen compared to treatment with CF or SF alone. Moreover, MIX further reduced levels of elevated serum testosterone, dihydrotestosterone, and prostate-specific antigen in BPH compared to the SP, a positive control. BPH was also improved more by MIX than by CF or SF alone. Based on the results, MIX is a potential natural therapeutic candidate for BPH by regulating 5α-reductase and AR signaling pathway.